Pendekatan Kritis terhadap Produksi Bioetanol Berbasis Eceng Gondok Eichhornia crassipes : Studi Literatur sebagai Dasar Pengembangan Pembelajaran Berbasis Proyek di SMA/SMK - Rodiatul Adawiyah; Muhammad Suwignyo Prayogo; Vivi Maratus Sholihah; Siti Waaqi’ah Khofidhotur Rofiah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2026)
This study aims to critically analyze bioethanol production from water hyacinth (Eichhornia crassipes) based on previous research findings and to develop a project-based learning design for SMA/SMK students. This study employs a qualitative approach using a literature review method by analyzing relevant scientific articles published in the last five years. Data were collected through documentation and analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that bioethanol production efficiency is strongly influenced by pretreatment methods, fermentation conditions, and process control, with yields generally categorized as low to moderate. Previous studies also reveal that project-based learning significantly enhances students’ conceptual understanding and critical thinking skills. Based on the synthesis of these findings, this study proposes a structured project-based learning design that integrates bioethanol production as a contextual learning medium. The implications of this study emphasize the importance of aligning technical feasibility, educational objectives, and sustainability principles in developing science-based learning projects in secondary education.